2019
DOI: 10.1002/mabi.201800356
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Spray‐Dried Polymer/Bacteria Microparticles for Electrospinning of Composite Nonwovens

Abstract: Spray Dried BiocompositesLiving Micrococcus luteus (M. luteus) and Escherichia coli (E. coli) are encapsulated in poly(vinyl alcohol), poly(vinylpyrrolidone), hydroxypropyl cellulose, and gelatin by high-temperature spray drying. The challenge is the survival of the bacteria during the standard spray-drying process at temperatures of 150 °C (M. luteus) and 120 °C (E. coli). Raman imaging and transmission electron microscopy indicate encapsulated bacteria in hollow composite microparticles. The versatility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The SEM analysis revealed that studied MPs exhibit a spherical shape with size heterogeneity in the range of 1 to 20 µm (Fig. 1 A), similarly as showed by Reich et al 60 . The presence of additives did not affect the size of developed microparticles, whereas the addition of Pluronic F-127 caused a slight collapse of their structure, similar to the report of Reich et al 60 .…”
Section: Resultssupporting
confidence: 83%
“…The SEM analysis revealed that studied MPs exhibit a spherical shape with size heterogeneity in the range of 1 to 20 µm (Fig. 1 A), similarly as showed by Reich et al 60 . The presence of additives did not affect the size of developed microparticles, whereas the addition of Pluronic F-127 caused a slight collapse of their structure, similar to the report of Reich et al 60 .…”
Section: Resultssupporting
confidence: 83%
“…and by a Raman‐atomic force microscopy (AFM) measurement. [ 22 ] In this study, the presence of M. luteus inside the PVA microparticles was shown. The diameter size of the PVA microparticles with encapsulated M. luteus is in the range of 2.58 ± 0.89 µm (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
“…introduced the encapsulation of bacteria in polymer microparticles by spray drying of gram‐positive and negative bacteria in different polymer solutions. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we showed the encapsulation of bacteria in PVA microparticles by advanced characterization method, such as Raman‐AFM. [ 19 ] Since some of these PVA microparticles also contained dead M. luteus , we analyzed the survival of M. luteus in additional steps using the live/dead analysis test and by differentiating the live and dead cells (microparticles with dead M. luteus cells [sample 3] were used as control samples for live/dead test).…”
Section: Resultsmentioning
confidence: 99%
“…[15,17,18] Reich et al reported the encapsulation of two different strains of bacteria in polymer particles prepared by spray drying. [19] Despite this, the uncontrolled release of bacteria from the particles is still a challenge, as is the uptake of nutrients for the bacteria in the particles. Indeed, bacteria were released from pure PVA particles immediately after contact with aqueous nutrient media.…”
Section: Introductionmentioning
confidence: 99%